Using a flocculent brewer’s yeast strain of Saccharomyces cerevisiae in the removal of heavy metals - Machado, Manuela D. (2008)
Fundação para a Ciência e a Tecnologia (FCT) - POCTI/CTA/47875/2002, (SFRH/BD/31755/2006)